LEKSIKON PERALATAN RUMAH TANGGA BERBAHAN BAMBU DI KABUPATEN PANDEGLANG (KAJIAN ETNOLINGUISTIK) - Ulfah, Lia Sa'adatul (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to categorize and characterize various household utensils made from bamboo in Pandeglang Regency; and explain the function of these products. Using bamboo as household equipment in Pandeglang Regency was the driving factor for conducting this research. Ethnolinguistic studies or methods that investigate the relationship between language and culture are the scope of this research. The focus of this research is the lexical form of household utensils and the function of bamboo household utensils in Pandeglang Regency. The method used in this research is a qualitative descriptive method that combines recording, discourse, and involvement approaches. A glossary of terms, descriptions of types of household equipment, and their uses are the subject of this research. The main informant and accompanying informants were interviewed in addition to observations to collect data. The evolution of the cultural lexicon can be influenced by cultural progress. The lexicon emerged along with human demands for product identification. The findings of this study resulted in a total of 35 lexicons, which can be divided into four groups: 28 lexicons representing monomorphemic household items, 3 lexicons representing polymorphemic household items, 1 lexicon representing rewords, and 3 lexicons representing phrases.